Propuesta para la declaración del rodeo tradicional del cantón Riobamba como patrimonio cultural intangible - Huilcapi Ocaña, Wilmer Paúl (2018)
The research work responds to the need to contribute, to the indigenous peoples and communities of the páramo being the rodeo the main activity of these peoples, the chagra as it is known is of vital importance for the haciendas there is born their customs and traditions implanted from the colony but with modernity have been losing space within society, with this project we want to rescue this tradition that is disappearing with the passing of years, the rodeo as such is essential for the chagras an ancient activity that is intended to rescue by declaring Cultural Heritage as a precaution for their existence and strengthening them so that the chagra and rodeo do not have an uncertain future but rather give it the value it has as an ancestral custom within the peoples that practice them as a way of daily life within of their daily activities and their economy to be able to subsist daily. The present research work intends to use as a methodological process, the registration form of the INPC for the safeguarding of the herd's patrimony, seeking the development of actions that are directed towards the revitalization, transmission, communication and diffusion of the patrimony, by means of the execution of: the identification, investigation and definition of safeguard actions. For this reason, it is intended to analyze and systematize both qualitatively and quantitatively the information collected, the INPC Record Card will be used as an instrument, the same one in which we will be able to carry data related to both material and immaterial elements. and be able to analyze them from a social, economic, and historical point of view, in order to give a value to the detour, to be able to obtain a safeguard, which allows us to declare it as Intangible Cultural Heritage in the canton Riobamba